The EMU debt criterion: an interpretation - BERNDSEN, R. (PSL Quarterly Review, 2013)
The convergence criteria specified in the Maastricht Treaty on government deficit and debt, inflation, the exchange rate and the long-term interest rate will play an important, if not decisive, role in determining which countries move on to the third stage of the Economic and Monetary Union (EMU). The aim of this work is to provide a possible interpretation of the EMU debt criterion. The author investigates the government debt criterion which, as Article 104c(2b) of the Treaty shows, has a considerable scope for interpretation. Although this subject has been discussed extensively, relatively little work has been done to develop a clear interpretation of the EMU debt criterion. A flexible approach is adopted in which parts of the relevant Treaty text are characterised using two parameters. JEL Codes: F02, F33, F36